Prevalence of dental caries among children in Misurata, Libya: a cross-sectional study (Journal of Academic Research, 2024)
This study was carried out to determine the prevalence rate of dental caries among Libyan children in Misurata City aged 3 to 13 years by determining the number of decayed, missing, and filled teeth (DMFT). A random sample was taken from 12 private primary schools in Misurata City attending summer camps from June to July 2023. The study included 332 children, who were examined by trained dentists. The number of male children was 209 (63.0%), and females were 123 (37.0%). In this study, children aged 3 to 6 years (75%) had decayed primary teeth, with a mean (d) component score of 3.409, compared to the decayed teeth (D) component in children aged 7 to 13 years, which recorded only 16.5% with a mean D score of 0.394. Missed and filled teeth were higher in preschool children compared to school children, showing (m) at 14%, (M) at 1%, (f) at 19%, and (F) at 3%. The prevalence of dental caries in children aged 7 to 13 years showed a high significant statistical association with age (P < 0.001). Additionally, a significant statistical relation was observed between the (D) component of DMFT and gender (P=0.007). The dmft index was recorded higher than the DMFT index (4.060; 0.457), respectively, showing that young children are affected more by dental caries. In Conclusion, Primary and secondary teeth have shown high rates of caries, indicating that dental caries remains a public health issue. Therefore, awareness should be provided to children, particularly at a young age.